2022
DOI: 10.1186/s12913-022-08512-2
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of health care professionals’ on delivering mHealth sexual and reproductive health services in rural settings in low-and-middle-income countries: a qualitative systematic review

Abstract: Background In low to middle income countries (LMICs) with limited health care providers (HCPs) and health infrastructure, digital technologies are rapidly being adopted to help augment service delivery. In this sphere, sexual and reproductive health (SRH) services are increasingly leveraging mobile health (mHealth) technologies to improve service and information provision in rural areas. This systematic review aimed to identify HCPs perspectives on barriers to, and facilitators of, mobile phone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…The right to privacy and the role of mHealth in ensuring privacy were mentioned in a systematic review of healthcare professional perspectives on mHealth-driven sexual and reproductive health (SRH) services in rural settings in LMICs, one of which was Cambodia. 55 The authors reported that compared to in-person health consultations mHealth services advance privacy, confidentiality, and trust. Although a Cambodia study was included in the review, the authors did not relate the privacy considerations to that study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The right to privacy and the role of mHealth in ensuring privacy were mentioned in a systematic review of healthcare professional perspectives on mHealth-driven sexual and reproductive health (SRH) services in rural settings in LMICs, one of which was Cambodia. 55 The authors reported that compared to in-person health consultations mHealth services advance privacy, confidentiality, and trust. Although a Cambodia study was included in the review, the authors did not relate the privacy considerations to that study.…”
Section: Resultsmentioning
confidence: 99%
“…The authors stated that SRH generally implies that people “have the capability to reproduce and the freedom to decide if, when, and how often to do so” and that mHealth specifically helps clients in making those health decisions, supporting freedom of choice. 55 …”
Section: Resultsmentioning
confidence: 99%
“…Their understandings and perspectives towards those with gender variant identities are also diverse ( 8 , 9 , 20 , 31 ). This group also reports varied levels of sexual health literacy ( 19 , 67 , 68 ), even when some of those perspectives reflect those of young adults growing up in countries with comprehensive sex education schemas ( 69 ).…”
Section: Literature Reviewmentioning
confidence: 99%